Representation of Orientalism in Sunsilk Print Advertising - Nurcahya, Hilma Rizky; Hafiar, Hanny; Nugraha, Aat Ruchiat (Jurnal The Messenger, 2018)
Using the qualitative method, the critical paradigm, and also Roland Barthes semiotic analysis, this study aims to find out the symbols contained in Sunsilk Co-creations print advertising, the meaning contained in the symbols and how the symbols subordinate the Eastern people. The results of this study indicate that there are seven symbols in Sunsilk Co-creations version print advertising that has unity meaning, i.e there are dominant people who are showed as more superior thus there are other people who are considered inferior. With the myth that the West is better seen as the superior and the East is seen as the inferior, then the symbols and meanings in Sunsilk Co-creations print advertising represent orientalism. The researchers suggest to pay attention to the symbols that will be aired so as not to be negative because it can affect the reputation of the company/institution concerned. Besides that, it is expected to the Eastern people especially Indonesian to be able to change their thought to be more proud and show their confidence.